Chinese Guideline for Diagnosis and Treatment of Co-morbid Insomnia and Obstructive Sleep Apnea (2024) - Chinese Academy Society of Sleep Medicine, Chinese Medical Doctor Association, Sleep Medicine Group, China Neurologist Association (Zhongguo quanke yixue)
When insomnia and obstructive sleep apnea (OSA) coexist, it is referred to as comorbid insomnia and obstructive sleep apnea (COMISA). The prevalence of COMISA in the general population ranges from 0.6% to 19.3%. It is primarily characterized by difficulty falling asleep, frequent nighttime awakenings, early morning awakening, poor sleep quality, snoring or apnea during sleep, unrefreshing or nonrestorative sleep, excessive daytime sleepiness, fatigue, attention impairment, memory impairment, emotional disorders, and impaired quality of life. COMISA can lead to adverse outcomes in multiple systems and increase all-cause mortality. Therefore, it is significant to establish a guidline for the diagnosis, differential diagnosis, and standardized treatment of COMISA. The guideline was organized by the Chinese Academy Society of Sleep Medicine, Chinese Medical Doctor Association and Sleep Medicine Group, China Neurologist Association. It was formed by reviewing domestic and international COMISA diagnosis and treatment practices, through literature evidence review, and after extensive discussion. The guideline summarized the epidemiology, etiology and risk factors, pathophysiological mechanisms, clinical manifestations, assessment methods, diagnosis, differential diagnosis, and treatment studies of COMISA, providing a basis for decision-making in the diagnosis and treatment of COMISA for clinician.